Self Efficacy: Form of Self-Confidence of Madrasah Aliyah Students in Dealing Anxiety in Memorizing Surah Al-Qur'an - Lilis Kurniawati; Edy Purwanto; Dyah Ayu Rahmawati (Universitas Negeri Semarang, 2023)
Anxiety of memorizing the Surah of Qur'an is response of the body such as feelings of pressure, fear, stress due to activity in memorizing the Surah of Qur'an which is characterized by certain feelings and symptoms that arise. As a result, students have difficulty in memorizing practices, resulting in suboptimal memorization. One solution to overcome this problem is have confidence in yourself be able organize and carry out all actions in order to achieve certain academic goals or called self-efficacy. This study aims determine the relationship between self efficacy and anxiety of memorizing the Surah of Qur'an. This study is a correlational quantitative study with the student population of State Madrasah Aliyah X amounting 940 students. Sampling using simple random samplingtechniques was obtained by 269 students. The data collection method uses self-efficacy scale made by researchers and academic anxiety scale of memorizing the results of adaptation (Lailatul Fiqriyah, 2020). Data analysis uses correlational person product moment correlation techniques to test the relationship between two variables. The results showed value (r) of -0.706 with p = 0.000 < 0.05, meaning that there was a significant negative relationship betwen self efficacy and anxiety of practice of memorizing the Qur'an surah in MAN students in qur'an and hadith lessons. The level anxiety of practice of memorization and self efficacy is in the moderate category. It is recommended for MAN students, one solution to be able reduce anxiety in practice of memorizing the Surah of Qur'an is to increase self-efficacy possessed.